The role of sex and ovarian hormones in hippocampal damage and cognitive deficits induced by chronic exposure to hypobaric hypoxia - Zhu, Dongyong; Zhang, Mengdi; He, Bo; Wan, Yixuan; Wang, Lei; Gao, Fabao (Frontiers in Neuroscience, 2022)
Purpose This study aims to investigate the role of sex and ovarian hormones in hippocampal damage and cognitive deficits and behavioral dysfunction in rats induced by chronic exposure to hypobaric hypoxia. Methods Six-week-old male and female SD rats were housed for 3 months either in a real altitude (4,250 m) environment as the model of chronic hypobaric-hypoxia (CHH) or in a plain as controls. The animal behavioral and hippocampal neurons at subcellular, molecular, and ultrastructural levels were characterized after CHH exposure. Results After 3 months of CHH exposure, (1) male CHH rats’ serum testosterone level was lower than male controls’ whereas female CHH rats’ serum estradiol level was higher than female controls’; (2) Morris water maze test finds that male rats showed more learning and spatial memory deficits than female rats; (3) male rats showed more severe hippocampal damage, hippocampal inflammation, oxidative stress and decreased hippocampal integrity (neurogenesis and dendritic spine density) than female rats; (4) Western blot analysis shows that, compared with the male control group, in male CHH group’s hippocampus, expression of nNOS, HO-1, and Bax protein increased whereas that of Bcl-2 protein decreased; (5) Expression of PON2 protein in male rats (CHH and controls) was lower than female rats (CHH and controls). In addition, CHH exposure decreased the expression of PON2 protein in both male and female rats; (6) qPCR analysis reveals that CHH exposure reduced the gene expression of N-methyl-D-aspartate receptor NR2A and NR2B subunits in male rats’ hippocampus. In addition, compared with the sham CHH group, the expression level of PON2 protein decreased in the OVX-CHH group’s hippocampus whereas oxidative stress, neuroinflammation, and degeneration of hippocampal neurons increased in the OVX-CHH group’s hippocampus. Conclusion After CHH exposure, male rats were significantly more likely than female rats to develop hippocampal damage, hippocampal neuroinflammation, and cognitive decline and deficits, suggesting that sex and ovarian hormones were significantly involved in regulating the rats’ susceptibility to CHH exposure-induced hippocampal damage.